To solve the equation −4(z + 12) = 36 for z, we must isolate the variable z.
First, we can distribute the -4 to both terms inside the parentheses:
-4z - 48 = 36
Next, we can add 48 to both sides of the equation to eliminate the -48 on the left side:
-4z = 36 + 48
-4z = 84
Finally, we can divide both sides of the equation by -4 to solve for z:
z = 84 / -4
z = -21
Therefore, the solution to the equation −4(z + 12) = 36 is z = -21.
What is the solution of the equation −4(z + 12) = 36 when solving for z%0D%0A%0D%0A?
1 answer